(untitled) (Research, Society and Development, 2021)
The present study reports a case of pathological root resorption in a primary molar treated endodontically with CTZ paste. A 7-year-old male patient sought care, accompanied by his parents, with the main complaint that the tooth had acute pain. During the anamnesis, the guardian reported that the tooth had been showing spontaneous pain that intensified during chewing. Clinical examination revealed no changes in the mucosa, gums and tongue. However, there was the presence of exposure of the pulp chamber of tooth 55, without evidence of pulp, configuring a clinical picture of necrosis. When performing the initial radiographic examination, it was possible to verify extensive caries lesion reaching the region of distal pulp horns and roots greater than 1/3 and the crown of the successor tooth not yet fully formed. Once the viability of maintaining tooth 55 in the oral cavity was verified, endodontic treatment was instituted using the LSTR technique with the CTZ antibiotic paste (chloramphenicol, tetracycline, zinc oxide) and restoration with composite resin. The patient was followed for a period of 3 and 12 months after the initial treatment.. In both visits, the restoration was healthy and satisfactory, however, it was possible to notice an increase in lateral root resorption and radiolucency in the furcation region. After confirming such resorption, the tooth had its indication for extraction. CTZ paste can stimulate the increase in rhizolysis speed in primary teeth through pathological root resorption. However, longitudinal studies need to be conducted.